THE IMPORTANCE OF THE TIME FACTOR IN THE ANALYSIS OF ECONOMIC PROCESSES (World Economics and Finance Bulletin, 2025)
The article summarizes economists scientists opinions about the role of the time factor in economy/ The author cons the time factor not only as a source of economy but alsoras one of the main elements of the usefulness of capital and consumer goods.